Penerapan Hedging di Perbankan Syariah sebagai Mitigasi Risiko Pasar Akibat Fluktuasi Kurs - Acep Samsudin; Rusdi Hidayat; Dwi Wulan Suci; Habib Ahmad; Rio Bastian; Bagus Firmansyah; Rafli Aprilian Firmansyah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
This research aims to determine the application of hedging in Islamic Banking Indonesia in mitigating the market risk resulting from fluctuations in foreign currency exchange rates. Researchers using qualitative methods, techniques Miles and Huberman Model. The object of this study is that adopted sharia hedging instrument of Conventional Banking products and prescribed and packaged in provisions DSN- MUI Fatwa No. 96/DSN-MUI/IV/2015, PBI 18/2/PBI/2016 and DPS Opinion No. 17/26/DPS/XII/2015 concerning the Proposed Transaction Hedging (Hedging) Sharia. The purpose and object of concern to researchers, then pure researchers took samples at PT. Bank Syariah Mandiri (BSM) that have implemented sharia hedging through forward contracts agreement. The results of this study, it can simply be concluded that the application of hedging has been implemented by BSM in accordancewith the provisions of both the provisions of the DSN-MUI, PBI and DPS. But on the other hand there are things that must be considered more serious for banks to implement sharia hedging instruments. This is because there is the inherent nature of the hedging diinstrument which is difficult to be avoided and eliminated. Keywords: Hedging, Forward Contract Agreement